Central Body of the Azotobacter Cyst - Parker, Laura T. (1966)
Parker, Laura T. (Louisiana State University, Baton Rouge), and M. D. Socolofsky. Central body of the Azotobacter cyst. J. Bacteriol. 91:297–303. 1966.—Sodium citrate was found to effect extensive rupture of cyst coats of Azotobacter vinelandii. By filtering a citrate-ruptured cyst suspension through a Millipore microfiber glass prefilter, a preparation of viable central bodies was obtained that contained less than 1% residual cysts and vegetative cells. Electron micrographs showed the central bodies to have a cell wall and cell membrane. Free central bodies germinated into typical vegetative cells. Central bodies exhibited approximately the same resistance to ultraviolet radiation, sonic treatment, and elevated temperatures as did vegetative cells; cysts were much more resistant. Manometric experiments indicated that central bodies and cysts have almost the same oxidative capabilities. Results of resistance studies indicated that the central body is a contracted vegetative cell encased in a protective coat. The cyst coat appears to account for the resistance of the cyst.